Model Perlindungan Korban Perdagangan Orang Dalam Sistem Hukum Pidana Indonesia - Jumiati, Jumiati; , Prof. Dr. Khudzaifah Dimyati, S.H., M.Hum; , Dr. Natangsa Surbakti, S.H., M.Hum (2015)
Up today, the enforcement effort against victims of trafficking in person only focuses on prevention efforts. In fact, the government has managed to reduce the level of human trafficking. However, the problems, the form of law that emphasizes on the protection of the victim does not get much attention. In other words, there has been no comprehensive effort in the legal protection through the recovery process and redress for victims. This study sought to determine 1) how the position of victim of trafficking in person in the Indonesian Criminal Justice system. 2) How the ideal model of legal protection for victims of trafficking in person. This research includes normative research, the approach used is statute approach. The technique of data analysis is to interpret and assess the data (state policy and other sources). This study states that the position of victims of human trafficking in the criminal justice system in Indonesia is still placed in a position that is not comparable to the offender. Attention of the criminal system is still too focused on criminal offenders than victims In addition the model protection of human trafficking victims in the criminal legal system in Indonesia is not comprehensive, resulting less opportunity for victims to get their rights. Although it has been guaranteed by Law No. 21 of 2007, their chance to get the rightis still very small.